Business Strategy Analysis Of Kelanting Riska Riski Home Industry In West Wetan Village Kabawetan District Kepahiang Regency - Nurul Khotimah; Ida Anggriani; Nirta Vera Yustanti (Penerbit Jurnal Indonesia, 2024)
The purpose of this study was to determine the analysis of the strategy of the Riska Riski household industry in West Wetan Village, Kabawetan District, Kepahiang Regency. The number of research samples was 40 people consisting of internal parties (1 owner and 3 employees), 36 external parties (25 stall owners and 11 consumers who came directly). The data analysis method used in this study is SWOT analysis is a tool used to find out opportunities, threats as well as the strengths and weaknesses of the company itself. One way to illustrate SWOT analysis is by using ETOP and SAP diagrams.The results of SAP analysis in this study include the strengths and weaknesses possessed by the internal Kelanting Riska Riski Home Industry obtained results of 4.36 with competition position criteria of 3.50-4.00 by being in intervals with dominant criteria, namely the company's position able to control the activities of strong competitors and able to master a wide selection of strategic alternatives. The results of the ETOP analysis show that the position of the Riska Riski Home Industry in West Wetan Village, Kabawetan District, Kepahiang Regency with an EOE value of 4.87 and an ETE value of 2.38 is in an ideal business position, namely a business that has a large main opportunity and a small main threat. This business has a high chance of success, this position is very profitable for the company. Based on SWOT, it can be explained that the strategy that can be carried out by the Kelanting Riska Riski Home Industry at the dominant and ideal meeting point, meaning that the right strategy is the SO (Strenght-Opportunity) strategy is a very profitable situation. Companies in this quadrant have opportunities and strengths so that they can take advantage of existing opportunities.